Analysis of A High Rise Building Frame Considering Hybrid Shear Wall Under Lateral Load Using ETABS A Review - Maninder Singh Bhatia; Pradeep Kumar Nirmal; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2022)
Shear dividers are primary components that safeguard structures from parallel loads like breeze and quakes. Whenever the outside dividers of a structure are inadequately solid and firm, shear dividers are added to the inside to give more noteworthy strength and solidness. At the point when the allowable range width proportion for the floor or rooftop stomach is surpassed, these shear dividers are required. Shear dividers are flexural individuals that are usually utilized in high-and low-ascent structures to forestall all out breakdown because of seismic burdens. Here half breed shear divider implies a blend of shear divider and X supporting This examination is engaged towards introducing the way of behaving of construction considering three unique cases to be specific, structure with X propping at corner, structure with shear divider at corner and design with crossover shear divider at corner. The construction was demonstrated and examined utilizing logical application ETABS v 2016. The boundaries of examination were Story relocation, story shear. Story float, story firmness and base shear.